Hospital Inpatient Information System at Siti Suaibah Clinic: Sistem Informasi Rawat Inap di klinik Siti Suaibah Sidoarjo - Sumarno Sumarno; Arief Wisaksono; Mochammad Luthfan Hakim; Riski Yulianto; Hindarto Hindarto (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to improve and expedite healthcare services for inpatients at Siti Suaibah Clinic in Krian. By implementing an effective Inpatient Information System, the study sought to provide accurate, efficient, and effective patient care. The research methodology involved data processing and analysis, resulting in several findings. The system facilitated patient data management, including medical histories, treatment schedules, and procedures. However, challenges such as development and maintenance costs, training for medical staff, and data security concerns were identified. Overall, the study highlights the benefits and implications of implementing the Inpatient Information System, emphasizing the need for careful planning and management. The outcome underscores the significance of optimizing healthcare services through innovative technology. Highlights: Improved patient care efficiency and effectiveness through the implementation of an Inpatient Information System. Challenges in implementing the system: development and maintenance costs, training for medical staff, and data security concerns. The significance of careful planning and management to optimize healthcare services and ensure the successful implementation of the Inpatient Information System. Keywords: Inpatient care, Information system, Healthcare services, Clinic, Implementation